Shaping rural regions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The conflicts and opportunities existing between local and global processes, and their impact on rural communities will be the main themes for discussion at the International Symposium on Globalisation and Local Development: Challenges to...